Heavy sulphur compounds, higher alcohols and esters production profile of Hanseniaspora uvarum and Hanseniaspora guilliermondii grown as pure and mixed cultures in grape must - Moreira, N. (2008)
Hanseniaspora guilliermondii and Hanseniaspora uvarum were tested in grape must fermentations as pure and mixed starter cultures with Saccharomyces cerevisiae. In pure cultures, the specific growth rates found were 0.29 h⁻¹ for H. uvarum, 0.23 h⁻¹ for H. guilliermondii and 0.18 h⁻¹ for S. cerevisiae. No significant differences were observed between these values and those obtained in mixed cultures. Results presented in this work show that growth of apiculate yeasts during the first days of fermentation enhances the production of desirable compounds, such as esters, and may not have a negative influence on the production of higher alcohols and undesirable heavy sulphur compounds. Growth of apiculate yeasts reduced the total content of higher alcohols in wines, when compared to those produced by a pure culture of S. cerevisiae. Furthermore, the highest levels of 2-phenylethyl acetate were obtained when H. guilliermondii was inoculated in grape musts, whereas H. uvarum increased the isoamyl acetate content of wines. Apiculate yeasts produced high amounts of ethyl acetate; however, the level of this compound decreased in mixed cultures of apiculate yeasts and S. cerevisiae. When S. cerevisiae was used as a starter culture, wines showed higher concentrations of glycerol, 2-phenylethanol and ethyl hexanoate. In mixed cultures of apiculate yeasts and S. cerevisiae, wines presented amounts of methionol, acetic acid-3-(methylthio)propyl ester, 4-(methylthio)-1-butanol, 2-mercaptoethanol and cis-2-methyltetrahydro-thiophen-3-ol similar to those produced by a pure culture of S. cerevisiae. An increase in the amounts of 3-(ethylthio)-1-propanol, trans-2-methyltetrahydro-thiophen-3-ol and 3- mercapto-1-propanol was obtained in wines produced from mixed cultures with H. guilliermondii.